Association between delay to coronary reperfusion and outcome in patients with acute coronary syndrome undergoing extracorporeal cardiopulmonary resuscitation. (May 2017) - Kuroki, Norihiro; Abe, Daisuke; Iwama, Toru; Suzuki, Kou; Sugiyama, Kazuhiro; Akashi, Akiko; Hamabe, Yuichi; Aonuma, Kazutaka; Sato, Akira
Abstract: Aim: The prognostic effect of early coronary reperfusion therapy with extracorporeal cardiopulmonary resuscitation (ECPR) in patients with cardiac arrest due to acute coronary syndrome (ACS) has yet to be clarified. We investigated the relationship between time interval from collapse to start of ECPR (CtoE) and coronary reperfusion (CtoR) time and neurological outcome in patients with cardiac arrest due to ACS. Methods: A cohort of 119 consecutive patients (63 ± 12 years old) with ACS who underwent ECPR and percutaneous coronary intervention(PCI) at our hospital was registered from January 2005 to June 2016. We analyzed patient clinical outcome, which was defined as survival with good neurological outcome at 30 days. We divided the patients into four groups according to CtoR time: Group 1 (time <60 min: n = 19), Group 2 (60 ≤ time < 90 min: n = 19), Group 3 (time ≥ 90 min: n = 70) and Group 4 (unsuccessful coronary reperfusion: n = 11). Results: One hundred patients (84%) were successful of PCI. A Kaplan–Meier curve showed that Group 1 had the best outcome among the four groups (good neurological outcome at 30 days; 74% vs 37% vs 23% vs 9%, P < 0.0001). In receiver operating characteristics analysis for good neurological outcome at 30 days, the cutoff values for CtoE was 40 min. The delay CtoE and CtoR time were independent predictors of poor neurological outcome at 30 days after adjusting multiple confounders (CtoE time; Hazard ratio (HR):1.026, 95% confidential intervals(CI): 1.011–1.042, P = 0.001), (CtoR time; HR: 1.004, 95% CI: 1.001–1.008, P = 0.020). Conclusions: A shorter CtoE and CtoR predicts better clinical outcome in patients with ACS undergoing ECPR.